PERLINDUNGAN HUKUM RAHASIA DAGANG ATAS INFORMASI BISNIS DALAM PERJANJIAN KERJA DI KABUPATEN SLEMAN: (Studi Cafe “Ideologi Cafe” di Sleman) - Faramukti, Talitha Shabrina (JIPRO: Journal of Intellectual Property, 2021)
This study aims to determine whether or not a trade secret legal protection for a business information in a cafenamely "Ideologi Cafe" in Sleman Regency and the steps to protect confidentiality of trade secrets needs to be carried out by every business actor so that the confidentiality of the trade secret is not disclosed by other parties who do not authorized. This step can be done in various ways, according to the with the terms and policies set by the cafe management. The formulation of the problem posed is: What are the steps? maintain the confidentiality of trade secrets on the cafe "Ideology Cafe" in the agreement work ?; What are the legal consequences for violations in serving confidentiality of trade secrets on the cafe "Ideology Cafe" in the employment agreement?. This research includes a typology of empirical legal research. Research data collected by means of document/library studies and interviews with owners cafe and cafe manager, then processed with the help of a descriptive program qualitative and the results are presented by bringing up conclusions with explanation. The analysis is carried out with a statutory approach combined with a sociological approach. The results of this study indicate that the legal protection of trade secrets at the cafe is enough, although on the other hand there are still weaknesses and lack. The drawbacks include the formal rules in the cafe has not fully protected the trade secret recipe; lack of knowledge management and employees have more regarding the Act Trade Secret which has governed everything confidential and have economic value. This study recommends the need for more socialization about Trade Secret Law due to lack of knowledge by the management and more stringent rules and all provisions which may result in the leakage of the trade secret.